Quality management system model: Building a sustainable school literacy culture - Rosidin, Asep; Herawan, Endang; Nurdin, Diding (Indonesian Research Journal in Education |IRJE|, 2025)
This research explored the necessity of a systematic approach to fostering a sustainable literacy culture in elementary schools. It developed a Quality Management System (QMS) to cultivate school literacy culture and enhance sustainable literacy quality. This research and development (R&D) used the PDCA model to develop an elementary school literacy program quality management system model. During the analysis stage, the researchers surveyed to assess and gauge the effectiveness of the previous program’s implementation. The design phase involved a literature review and analysis of survey results, referring to literature, and consulting experts. The findings indicated that implementing the QMS model significantly aids primary schools in achieving a sustainable literacy culture. This research’s primary contribution lied in the QMS model, offering a structured framework for elementary schools to enhance sustainability literacy. This model contributes to theoretical understanding and practically supports the ongoing development of a strong, effective literacy culture in primary education settings.